Laporan Pelaksanaan Anggaran untuk Mengukur Kinerja Finansial pada Organisasi Sektor Publik - Haerani, Anggi; Prihatin, Khristina Sri; Irnawati, Erni (FKIP, Universitas Banten Jaya, 2025)
Society today is concerned about the performance of government agencies. There is often a public distrust of government, due to the fact that public agencies often use funds without proper planning, overspend, make frequent losses and do not always achieve set goals. The purpose of submitting financial statements in the public sector is to convey information about the resources, location, and use of funds. The information gathering strategies used by the researcher in this study included a literature review and field observations. In the process of data analysis, the author applied two approaches, namely descriptive method and deductive approach. from an economic point of view budget execution report to measure financial performance in public sector organisations is less economical because the realised expenditure is greater than the efficiency target. Some entities have improved efficiency over time by managing expenditure better than the target. While in terms of effectiveness, this shows the agency's ability to achieve the set revenue target, although some entities such as the Medan City Government have not been able to realise all potential revenue.